2017
DOI: 10.1002/ange.201611024
|View full text |Cite
|
Sign up to set email alerts
|

Silver‐Catalyzed Chemoselective [4+2] Annulation of Two Isocyanides: A General Route to Pyridone‐Fused Carbo‐ and Heterocycles

Abstract: A silver‐catalyzed chemoselective [4+2] annulation of aryl and heteroaryl isocyanides with α‐substituted isocyanoacetamides was developed for the facile and efficient synthesis of 2‐aminoquinolones, naphthyridines, and phenanthrolines. A mechanism for this multistep domino reaction is proposed on the basis of a 13C‐labeling experiment, according to which an unprecedented chemoselective heterodimerization of two different isocyanides generates an α‐amidoketenimine intermediate, which undergoes 1,3‐amino migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Although several o ‐functionalized arylisocyanides, such as o ‐alkenyl, alkynyl, acyl, aryl,, cyano, halo, methoxycarbonyl and aminocarbonyl arylisocyanides, have been employed for the synthesis of diverse class of benzo‐fused heterocycles, to our knowledge, the synthetic utility of o ‐enoyl arylisocyanides have barely been exploited . We recently reported the only transformation of o ‐enoyl arylisocyanides, i. e., o ‐cinnamoyl phenylisocyanide, as functionalized arylisocyanides in the chemoselective [4+2] annulation of two different isocyanides . However, in this reaction, the cinnamoyl group was intacted.…”
Section: Methodsmentioning
confidence: 99%
“…Although several o ‐functionalized arylisocyanides, such as o ‐alkenyl, alkynyl, acyl, aryl,, cyano, halo, methoxycarbonyl and aminocarbonyl arylisocyanides, have been employed for the synthesis of diverse class of benzo‐fused heterocycles, to our knowledge, the synthetic utility of o ‐enoyl arylisocyanides have barely been exploited . We recently reported the only transformation of o ‐enoyl arylisocyanides, i. e., o ‐cinnamoyl phenylisocyanide, as functionalized arylisocyanides in the chemoselective [4+2] annulation of two different isocyanides . However, in this reaction, the cinnamoyl group was intacted.…”
Section: Methodsmentioning
confidence: 99%
“…To our surprise, α-substituted isocyanoacetamides 2g cyclocyclised with aryl isocyanides 2c gave an unprecedented result under silver catalysis, instead of preparing various 2-aminoquinolones 9 in 35-80% yields. 20 In this reaction, the new reactivity profiles were exhibited by the generation of α-amidoketenimines 12 through the heterodimerization of two different isocyanides. As presented in Scheme 3, the key intermediate 12 is derived from removal of an isocyano group in intermediate 11.…”
Section: Cyclization With α-Methenyl Isocyanidesmentioning
confidence: 99%
“…[4] In addition, imidzaoles can catalyze organic reactions by themselves. [7,8] The "C=N" bond of imines, [7a] carbodiimides, [7b] isothiocynates, [7c,d] benzothiazoles, [7e] ketenimines, [7f] and isocyanides [8] have been succesfully appied to [3 + 2] cycloaddition to construct imidazoles (Scheme 1, a). [6] In these methods, the [3 + 2] cycloaddition of active methylene isocyanides and "C=N" is a highly atomic economic method.…”
mentioning
confidence: 99%
“…When CuTC applied to the reaction instead of Cu 2 O, the reaction proceed smoothly to give 4 a in 64% yield (Table 1, entry 2). Screening different amounts of the Cu 2 O revealed that 15 mol% of Cu 2 O was the ideal amount ( Table 1, entries [8][9]. However, all these catalysts were not effective.…”
mentioning
confidence: 99%
See 1 more Smart Citation